Effect of polysaccharide fractions from Fortunella margarita on the fecal microbiota of mice and SCFA production in vitro - Peilin Chen; Suzhen Lei; Mingyao Tong; Qing Chang; Baodong Zheng; Yi Zhang; Hongliang Zeng (Food Science and Human Wellness)
Fortunella margarita polysaccharides (FMPS) are composed of 4 polysaccharide fragments, namely mannogalactoglucan, galactoglucan, glucan and arabinoglucan. This study investigated the in vitro fermentation of FMPS fractions and their effect on the fecal microbiota of mice and short chain fatty acids (SCFAs) production. The results showed that the structure of the fecal microbiota was changed after FMPS fermentation. At the phylum level, the polysaccharide fractions reduced the relative abundance of Bacteroidetes compared with the inulin group. At the genus level, the polysaccharide fractions increased the abundance of Lactobacillus, and decreased the abundance of Granulicatella, Proteus and Rummeliibacillus. Polysaccharide fractions could promote the proliferation of beneficial bacteria (Lactobacillus), and decreased harmful bacteria (Granulicatella, Proteus, Rummeliibacillus and Serratia). Furthermore, there was a significant distinction in the genus level flora processed by different polysaccharide fractions, especially mannogalactoglucan. Polysaccharide fractions showed potential prebiotic effects, with mannogalactoglucan, in particular, promoting proliferation of SCFA-producing bacteria. SCFAs were regulated by monosaccharide composition, molecular weight of the FMPS fractions, and the composition of the fecal bacteria. Polysaccharide fractions could modulate metabolic function of the fecal microbiota, altering the levels of SCFAs. These results suggested that FMPS are important functional components in gut health, especially mannogalactoglucan.